Island. Book three, Escape - Korman, Gordon (New York : Scholastic, 2001)
Six kids stuck alone on a desert island after a shipwreck need help because one is seriously injured and though they think they are alone, there is a dangerous group on the island.
"An Apple paperback."
620
Accelerated Reader AR
Keywords: Shipwrecks -- Juvenile fiction